Design, Development, and Method Evaluation of Aptamer-Based Diagnostics for the Detection of Multidrug-Resistant Bacteria - N. Jaya Lakshmi; Hariprasad Puttaswamy (Proceedings)
Bacterial multidrug resistance poses a growing hazard to public health worldwide. Pseudomonas aeruginosa is a ubiquitous bacterial species that has been identified as the second most critical pathogen on the list of drug-resistant bacteria posing a huge threat to human health. P. aeruginosa is an opportunistic Gram-negative bacterium that rapidly produces multiple virulence factors that promote adhesion, host cell penetration, and pathogenicity. It possesses inherent resistance to multiple classes of antibiotics, evading antibiotic treatment by triggering the persister phenotype. Traditional approaches for detecting pathogens in laboratory and clinical settings primarily involve microbiological, nucleic acid-based, immunological, and sequencing techniques, among others. These procedures are time-consuming, necessitate advanced laboratory equipment and skilled staff, and incur large setup costs, rendering them unsuitable for on-the-spot detection of bacterial infections in settings with limited resources. Aptasensors utilize nucleic acid aptamers as bio-receptors to detect pathogens. They circumvent the existing limitations of conventional detection systems due to their sensitivity, versatility for modification, cost-efficiency, and ability to enable real-time detection. So far, as per the literature, three aptamers have been developed against P. aeruginosa using whole bacterial cells but with unreported binding sites. This study aims to identify highly specific aptamers that can bind specifically to P. aeruginosa using whole-bacterium SELEX at any stage of growth with an extensive study of binding site interaction and identification. The objective is to develop an aptamer-based kit enabling rapid point-of-care detection of P. aeruginosa in clinical and environmental samples.